Potenciales evocados y cognición - Muñoz Gamboa., Caupolicán; Jiménez Cruz., Joel (Revista Mexicana de Ingenieria Biomedica, 2007)
In this paper a special kind of evoked potentials, known as endogenous potentials, is presented. They are consequence of a controlled sensorial stimulus and, at the same time, are associated to internal psychological processes that have been triggered by the external stimulus. Therefore, they are products of the brain processing due to the stimulation. For this kind of PE the physiological origin is analyzed, several forms of stimulation are described for every one of them, the morphology of the signals is specified, some of the most important characteristics and properties are remarked as well as some of their most common clinical applications are detailed.